Factorial Study Of The Importance Of Speed, Agility and Body Traits In Youth Badminton Player - Nabhan, Nada (Journal of Physical Education, 2010)
Each sport activity requires different physical traits than other activities. Badminton is one of the sports that require high level of effort to achieve great performance. Anthropometric measurements are considered good indicators of great performance. The importance of the study lies in specifying statistically based indicators using factorial analyses to achieve accurate results though studying strength, speed and bodily traits of badminton players. The aims of the research are: 1. Specifying a group of measurements that represent the concluded factors that can be used to describe bodily – physicals variables of badminton players. 2. Specifying factorial analyses for bodily tests and anthropometric measurements for young volleyball players. The research was applied on 50 young volleyball players of the ages 14 – 16 years old for the academic year 2009. The research involved applying 6 physical tests to measure speed and agility and 19 anthropometric measurement tests. Factorial anises using essential components for Harold Holtnge and eight factors were concluded. Many factors were accepted like factor one id the upper body length, second factor is speed, third factor is body girth, the forth factor is lower body length and the sixth factor is agility. Factors number five, seven and eight were all ignored. Many variables have been selected as follows factor one is the length of the upper arm, forearm and arm, second factor is 50 m running from high start, 15sec spot running, 30m running from a moving start, the third factor the chest girth and abdomen girth, forth factor is leg, thigh and shin lengths and finally the sixth factor is zigzag running, shuttle run and circular run